Notes on the type material of Compsobuthus acutecarinatus (Simon, 1882) and C. maindroni (Kraepelin, 1900), and description of a new species from United Arab Emirates: Scorpiones: Buthidae - Lourenço, Wilson R.; Leguin, Elise-Anne; Duhem, Bernard (Zoology in the Middle East, 2010)
Two species of the genus Compsobuthus Vachon, 1949, C. acutecarinatus (Simon) and C. maindroni (Kraepelin), have been the subject of several publications in the last three decades. Nevertheless, some doubts remain about their precise identity and range of geographic distribution. We give here precise re-diagnoses in the light of the type material now clearly identified. The holotype of C. acutecarinatus is properly illustrated and measured. A lectotype is designated for C. maindroni, from the large syntype series. A new species of Compsobuthus is also described from United Arab Emirates.